Antidepressants-Associated Sexual Dysfunction: Impact, Effects and Treatment - NASH, MICHAEL; HIGGINS, AGNES; LYNCH, AILEEN (My University, 2010)
Sexual dysfunction is a common side effect of antidepressants and can have significant impact on the person?s quality of life, relationships, mental health, and recovery. The reported incidence of sexual dysfunction associated with antidepressant medication varies considerably between studies, making it difficult to estimate the exact incidence or prevalence. The sexual problems reported range from decreased sexual desire, decreased sexual excitement, diminished or delayed orgasm, to erection or delayed ejaculation problems. There are a number of case reports of sexual side effects, such as priapism, painful ejaculation, penile anesthesia, loss of sensation in the vagina and nipples, persistent genital arousal and nonpuerperal lactation in women. The focus of this article is to explore the incidence, pathophysiology, and treatment of antidepressant iatrogenic sexual dysfunction
PUBLISHED
Keywords: Sexual dysfunction